An Analysis of Psychological Resilience and Secondary Trauma Among Psychologists Involved in the Earthquake Response in Kahramanmaraş - Demirel, Burcu; Kökrek, Zekeriya (The Bulletin of Legal Medicine, 2024)
Objective: The aim of this study is to examine the relationship between the psychological resilience levels and secondary trauma levels of mental health professionals who were involved in the Kahramanmaraş-centered earthquake on February 6. Additionally, the study investigates whether psychological resilience and secondary trauma levels vary based on demographic factors.Methods: Psychological resilience has been shown to negatively predict secondary traumatic stress (β=-0.412; t=-5.034; p
Keywords: Mental Health Professionals; Psychological Resilience; Secondary Trauma; Secondary Traumatic Stress; Earthquake